2016
DOI: 10.1585/pfr.11.2401080
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten-Surface-Structure Dependence of Sputtering Yield for a Noble Gas

Abstract: Using the binary-collision approximation simulation with atomic collision in any structured target code AC∀T, we calculated sputtering yield, range, and retention rate for tungsten with a rough surface under argon atom irradiation. The simulation revealed the sputtering yield decreases and the retention rate increases as the surface becomes rougher. Because these quantities strongly depend on the surface, we suggest that it is necessary to consider the surface structure of the tungsten target when estimating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Thus, it was found that the physical quantities for sputtering phenomena depend strongly on the crystalline orientation of the tungsten surface. On the other hand, by our previous work [8], we have shown that the physical quantities also depend on the roughness of the tungsten surface. Considering the above two results, we propose that it is necessary to consider the structure of the target surface more exactly than the "flat" and amorphous structured surface model which is popular in order to evaluate the endurance of plasma facing material.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Thus, it was found that the physical quantities for sputtering phenomena depend strongly on the crystalline orientation of the tungsten surface. On the other hand, by our previous work [8], we have shown that the physical quantities also depend on the roughness of the tungsten surface. Considering the above two results, we propose that it is necessary to consider the structure of the target surface more exactly than the "flat" and amorphous structured surface model which is popular in order to evaluate the endurance of plasma facing material.…”
Section: Resultsmentioning
confidence: 74%
“…In our previous work [8], we investigated the dependence of the sputtering phenomena on the surface roughness, based on the experiment that was performed by Nishijima et al [3]. According to their work, the sputtering yield depends on the surface roughness, that is, the thickness of the fuzz layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamics (MD) [10][11][12][13][14][15][16][17][18][19][20][21][22][23], the binary collision approximation (BCA) [21,24,25], and several models [26,27] have been employed in simulations aimed at understanding the formation of fuzzy nanostructures. In particular, multi-scale simulations [28] are necessary to treat such complex processes as helium bubble formation and the growth of fuzzy nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…The same procedure was used to skip the injection process in a full MD simulation of helium bubble formation [31]. However, the change in the injection process between a flat surface and a rough grown surface cannot be represented by this approach because BCA simulations have shown that the penetration depth, reflection ratio, and sputtering yield depend strongly on the surface morphology [24,25]. In addition, the BCA-MD hybrid simulation has shown that injected helium atoms are easily stopped in helium bubbles [32].…”
Section: Introductionmentioning
confidence: 99%